Ethics in Public Health Research Masters of Marketing: Bringing Private Sector Skills toPublic Health Partnerships - Valerie A. Curtis, , Nana Garbrah-Aidoo, , Beth Scott (American Journal of Public Health | April 2007, Vol 97, No. 4, 2007)
Skill in marketing is a scarce resource in public health, especially in developing countries. The Global Public-Private Partnership for Handwashing with Soap set out to tap the consumer marketing skills of industry for national handwashing programs.Lessons learned from commercial marketers included how to (1) understand consumer motivation, (2) employ 1 single unifying idea, (3) plan for effective reach, and (4) ensure effectiveness before national launch. After the first marketing program, 71 per cent of Ghanaian mothers knew the television ad and the reported rates of handwashing with soap increased. Conditions for the expansion of such partnerships include a wider appreciation of what consumer marketing is, what it can do for public health, and thepotential benefits to industry. Although there are practical and philosophical difficulties,there are many opportunities for such partnerships